Peran Strategis Manajemen SDM - I Gusti Ngurah Agung Gede Sastra Bahu (FEB Universitas Maritim Semarang, 2024)
Human Resource Management (HRM) is a strategic field that plays a crucial role in achieving organizational goals. HRM is not just about managing people, but also requires knowledge of human behavior and the ability to manage it effectively. The formulation of techniques in HRM must be relevant to the business methodology used by the organization. HRM is not just a science, but also an art in the business world. HRM aims to regulate the relationship and role of manpower to be effective and efficient, so that it can help achieve the goals of the company, employees, and society.